Pilot Study On Pharmaceutical Waste Disposal and Its Role in Sustainable Management - Piekara, Agnieszka (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Significant attention is being given to waste management worldwide, with efforts to reduce waste volumes. While plastics receive the most focus, pharmaceuticals also pose a significant environmental threat. This pilot study on pharmaceutical waste disposal, conducted at a pharmacy in Poland, includes quantitative and qualitative analyses of medicines returned for disposal in two-week intervals. The research provides information about customer practices, revealing that many unexpired medicines are often found in disposal bins, further emphasizing the need for better education. The findings offer valuable insights into the role of pharmaceutical waste management in sustainable practices, addressing the environmental challenges posed by improper disposal. Furthermore, this study highlights the critical responsibility of pharmaceutical manufacturers to ensure the safe and sustainable disposal of their products. Additionally, the improper disposal of pharmaceutical waste generates a significant financial burden on national health systems, further underscoring the importance of responsible waste management practices.